Technology management, transaction processes and governance structures - Siriram, Rajenall (My University, 2003)
This thesis focuses on technology management within and between firms. The effects of technology management on transaction processes, and the mechanisms for effective governance of technology is studied. A model incorporating different schools of thought including technology management, strategic management, organizational and TCE (transactional cost economics) and operations management is built. The model has subsets of technology management, transaction processes, and governance structures. The model is then tested within an investigative framework, which includes organizational determinants, competitors, and external factors. The testing is on firms that adopt or implement technologies. Technological firms are categorized into user firms and system integrator firms. User firms are firms that adopt technologies; system integrator firms are firms that are involved in the implementation of technologies and help user firms. Statistical analysis is used to test correlations between these two types of technological firms. An expert panel is used to understand the differences and similarities between the two types of technological firms. Different links are significant in this model and the following conclusions may be drawn: firstly that technology management, transaction processes and governance structures are linked; secondly that the transaction cost economic view and the resource-based view are both important for competitive advantage and neither is superior to the other; and thirdly that the effects of technological change on the organizational and environmental evolution is significant. This thesis lays the foundation for further work toward integrating technology management, transaction processes, and governance structures. In addition lessons for managers involved in technological decisions are also provided.
A thesis submitted to the Faculty of Engineering and the Built Environment, University of the Witwatersrand, Johannesburg, in fulfillment of the requirements for the degree of Doctor of Philosophy.
Keywords: Technology management.; Operations research.; Production management.